1994
DOI: 10.1007/bf00317317
|View full text |Cite
|
Sign up to set email alerts
|

Offspring fitness in relation to population size and genetic variation in the rare perennial plant species Gentiana pneumonanthe (Gentianaceae)

Abstract: Offspring fitness in relation to population size and genetic variation in the rare perennial plant species Gentiana pneumonanthe (Gentianaceae) Oostermeijer, J.G.B.; van Eijck, M.W.; den Nijs, J.C.M. Published in: Oecologia DOI:10.1007/BF00317317 Link to publication Citation for published version (APA):Oostermeijer, J. G. B., van Eijck, M. W., & den Nijs, J. C. M. (1994). Offspring fitness in relation to population size and genetic variation in the rare perennial plant species Gentiana pneumonanthe (Gentianace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
169
5
8

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(194 citation statements)
references
References 33 publications
12
169
5
8
Order By: Relevance
“…However, some studies show that the levels of genetic diversity within populations are not positively correlated with population size (e.g. LESSICA and ALLENDORF, 1992;ELLSTRAND and ELAM, 1993;OOSTERMEIJER et al, 1994;GODT et al, 1995). Such a situation happened in the case of our study.…”
Section: Discussioncontrasting
confidence: 65%
“…However, some studies show that the levels of genetic diversity within populations are not positively correlated with population size (e.g. LESSICA and ALLENDORF, 1992;ELLSTRAND and ELAM, 1993;OOSTERMEIJER et al, 1994;GODT et al, 1995). Such a situation happened in the case of our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Numerous studies of plants (and animals) have recorded reduced fitness in small populations in nature and when individuals from small populations are raised in a common environment (Menges, 1991;Oostermeijer et al, 1994;Heschel and Paige, 1995;Fischer and Matthies, 1998;Morgan, 1999;Fischer et al, 2000a;KĂ©ry et al, 2000;Luijten et al, 2000;Schmidt and Jensen, 2000;Mavraganis and Eckert, 2001;Jacquemyn et al, 2002;Paschke et al, 2002;Severns, 2003;Vergeer et al, 2003;Brys et al, 2004). There are three likely genetic causes for reduced fitness of plants from smaller populations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, several previous works (e.g. Ouborg et al, 1991;Oostermeijer et al, 1994) demonstrated a positive relationship between population size and variation in fitness components for rare perennial plant species. Similar results were obtained in Acacia tortilis subspecies raddiana populations growing in the same habitats (Zaghloul, 2008).…”
Section: Discussionmentioning
confidence: 75%